Noble society five lives from twelfth-century Germany - Lyon, Jonathan R. 1974- (Manchester Medieval Sources Series, 2017)
This book provides scholars and students alike with a set of texts that can deepen their understanding of the culture and society of the twelfth-century German kingdom. The sources translated here bring to life the activities of five noblemen and noblewomen from Rome to the Baltic coast and from the Rhine River to the Alpine valleys of Austria. To read these five sources together is to appreciate how interconnected political, military, economic, religious and spiritual interests could be for some of the leading members of medieval German society-and for the authors who wrote about them. Whether fighting for the emperor in Italy, bringing Christianity to pagans in what is today northern Poland, or founding, reforming and governing monastic communities in the heartland of the German kingdom, the subjects of these texts call attention to some of the many ways that noble life shaped the world of central medieval Europe